THE RELATIONSHIP OF PROVIDING EDUCATION ON THE USE OF SELF-MEDICATION DRUGS (Pain, Flu, Faver, Cough) ON THE LEVEL OF KNOWLEDGE OF VISITORS TO ANUGERAH BLUTO MEDIKA PHARMACY IN THE BLUTO SUB-DISTRICT AREA IN 2023 - Walujo, Djembor Sugeng; Farida, Umul; Putri, Jinani Firdausi (Jurnal Wiyata Penelitian Sains dan Kesehatan, 2024)
Education is an activity or effort to deliver health messages to the community, groups, or individuals. Self-medication is a largely community-based effort to overcome disease symptoms before seeking help from health workers. This research aims to determine the influence of providing education on the use of self-medication drugs on the level of knowledge of visitors to Anugerah Bluto Medika Pharmacy in the Bluto Sub-District area. Pre-experimental research with a one group pretest-posttest research design was conducted by comparing the patient's self-medication knowledge before and after being given education using leaflets. The sampling technique used was target sampling with inclusion and exclusion criteria. The sample size consisted of 100 respondents. The results showed that the level of knowledge of pharmacy visitors showed good (11%), sufficient (22%), less (67%) after being given counseling showed good (97%), sufficient (1%), less (2%). ). ). The results of the Chi-Square test obtained a significant value of 0.337 > 0.05 which indicates that there is no relationship between the provision of education and the level of knowledge about the use of self-medication.